Learning From Crisis: Post-Crisis Evaluation and Organizational Resilience - Angia Sulaeman (Universitas KH. Abdul Chalim Mojokerto, 2026)
In an organization, failure is an inevitable occurrence. Organizational responses reflect a form of learning that is expected to improve organizational quality in the post-crisis period. Organizations are required to integrate crisis communication at both managerial and operational levels in order to create synergy and develop effective strategies for dealing with future crises and recovery the image that caused by the previous crisis. Therefore, post-crisis evaluation is essential as a learning process for anticipating and managing future crises and should be carried out at all levels of the organization. Based on a literature review on post-crisis evaluation and organizational resilience, effective post-crisis management requires the development of multi-level resilience, transparency and integration of crisis communication, leadership integration, knowledge management, organizational learning, and post-crisis handling aimed at rebuilding trust and organizational reputation. By establishing a comprehensive crisis evaluation process, organizations are expected to restore public legitimacy and trust.